Rhinochelys amaberti Moret (1935), a protostegid turtle from the Early Cretaceous of France - Isaure Scavezzoni; Valentin Fischer (PeerJ, 2018)
Modern marine turtles (chelonioids) are the remnants of an ancient radiation that roots in the Cretaceous. The oldest members of that radiation are first recorded from the Early Cretaceous and a series of species are known from the Albian-Cenomanian interval, many of which have been allocated to the widespread but poorly defined genus Rhinochelys, possibly concealing the diversity and the evolution of early marine turtles. In order to better understand the radiation of chelonioids, we redescribe the holotype and assess the taxonomy of Rhinochelys amaberti Moret (1935) (UJF-ID.11167) from the Late Albian (Stoliczkaia dispar Zone) of the Vallon de la Fauge (Isère, France). We also make preliminary assessments of the phylogenetic relationships of Chelonioidea using two updated datasets that widely sample Cretaceous taxa, especially Rhinochelys. Rhinochelys amaberti is a valid taxon that is supported by eight autapomorphies; an emended diagnosisis proposed. Our phylogenetic analyses suggest that Rhinochelys could be polyphyletic, but constraining it as a monophyletic entity does not produce trees that are significantly less parsimonious. Moreover, support values and stratigraphic congruence indexes are fairly low for the recovered typologies, suggesting that missing data still strongly affect our understanding of the Cretaceous diversification of sea turtles.